2005
DOI: 10.1152/ajprenal.00188.2005
|View full text |Cite
|
Sign up to set email alerts
|

CytochromeP-450-dependent metabolism of arachidonic acid in the kidney of rats with diabetes insipidus

Abstract: . Cytochrome P-450-dependent metabolism of arachidonic acid in the kidney of rats with diabetes insipidus. Am J Physiol Renal Physiol 289: F1333-F1340, 2005. First published July 12, 2005 doi:10.1152/ajprenal.00188.2005.-This study compared the renal metabolism of arachidonic acid in Brattleboro (BB) (vasopressin deficient) and Long-Evans (LE) control rats and the effects of a cytochrome P-450 (CYP) inhibitor 1-aminobenzotriazole (ABT) on renal function in these animals. The production of 20-hydroxyeicosatetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The observed reduction of outer medullary iPLA 2 ␤ levels in dDAVP-treated DI rats as well as the pharmacologically induced inhibition of iPLA 2 ␤ in mTAL cells are therefore likely to result in a decrease in 20-HETE, which in turn may cause an activation of NKCC2. In line with this assumption, earlier studies have shown an increased capacity for 20-HETE synthesis in outer medullary tissue preparations from DI rats that was reduced by dDAVP treatment (36).…”
Section: Discussionsupporting
confidence: 54%
“…The observed reduction of outer medullary iPLA 2 ␤ levels in dDAVP-treated DI rats as well as the pharmacologically induced inhibition of iPLA 2 ␤ in mTAL cells are therefore likely to result in a decrease in 20-HETE, which in turn may cause an activation of NKCC2. In line with this assumption, earlier studies have shown an increased capacity for 20-HETE synthesis in outer medullary tissue preparations from DI rats that was reduced by dDAVP treatment (36).…”
Section: Discussionsupporting
confidence: 54%
“…The predominant CYP450 in the kidney cortex that synthesizes 20-HETE is cytochrome P450 of the 4A family (CYP4A) ( 19 – 21 ). 20-HETE has multiple and opposing functions depending on the site of production and target cells/tissues ( 19 , 22 24 ).…”
mentioning
confidence: 99%
“…Other vasoactive mediators that have been implicated in the regulation of AVP signalling in the renal medulla include angiotensin 2, endothelin, ATP, adenosin and eicosanoids such as 20‐HETE and EETs (Sarkis et al . , Stricklett et al . , Dobrowolski et al .…”
Section: Discussionmentioning
confidence: 99%